Combination of Imperfect Data in Fuzzy and Probabilistic Extension Classes - Dantan, Jérôme; Pollet, Yann; Taibi, Salima (Journal of Environmental Accounting and Management, 2026)
In this article, we propose a uniform formal model able to handle uncertain data. The approach presented provides a formalism for both representing and manipulating rigorously quantities which may have a finite number of possible or probable values with their interdependencies. Then, we define an algebraic structure to operate chained computations on such quantities with properties similar to 兟 . Next, we provide a particular interpretation for mixing such quantities through the Dempster- Shafer theory. Finally, we provide an implementation of this approach into object oriented programming.